2022
DOI: 10.1108/ijoes-04-2022-0086
|View full text |Cite
|
Sign up to set email alerts
|

Fostering individual behavior through quality of life variables: the role of Islamic work ethics

Abstract: Purpose The increasing ethical misconduct at job place demands to understand the role of ethics in a wide variety of disciplines. This paper aims to empirically investigate the mediating mechanism of life satisfaction and subjective happiness between Islamic work ethics – innovative work behavior (IWB) and organizational citizenship behavior (OCB). Design/methodology/approach The sample comprised 296 employees and 58 head of departments (HODs) of top 11 business schools in Pakistan. The data of the study wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 81 publications
1
17
0
2
Order By: Relevance
“…The results showed that workplace happiness positively affected innovative work behavior. These results support previous studies [16,[57][58][59]. In other words, innovative work behavior would coherently increase when lecturers felt continuously and increasingly happy at work.…”
Section: The Effect Of Workplace Happiness On Innovative Work Behaviorsupporting
confidence: 91%
See 1 more Smart Citation
“…The results showed that workplace happiness positively affected innovative work behavior. These results support previous studies [16,[57][58][59]. In other words, innovative work behavior would coherently increase when lecturers felt continuously and increasingly happy at work.…”
Section: The Effect Of Workplace Happiness On Innovative Work Behaviorsupporting
confidence: 91%
“…Happy employees can also show positive attitudes and behaviors, which can influence other employees at work, thus providing a broad overview of innovative work behavior [16,57,58]. Furthermore, a study of Zia, Naveed [59] on employees of full-time business universities/HEIs in Pakistan uncovered that workplace happiness affected innovative work behavior. Thus, based on the studies and discussion above, the researchers predicted that:…”
Section: Workplace Happiness and Innovative Work Behaviormentioning
confidence: 99%
“…There are various studies on the role of Islamic work ethics in multiple things in organizational activities and the environment. Islamic work ethics has an influence on work outcomes (Rokhman, 2010), OCB (Murtaza et al, 2016;Zia et al, 2022), conscientiousness, agreeableness, extraversion, opennessto-experience and emotional instability of employees (Wahab, 2017), leadership (Javed et al, 2020), and knowledge sharing behavior (Javaid et al, 2022;Murtaza et al, 2016).…”
Section: Islamic Work Ethicmentioning
confidence: 99%
“…Particularly, the characteristic of organizational members with OCB is that they are oriented towards innovative performance, so it can directly impact the survival and improvement of organizational performance in a competitive environment to remain superior. (Dubey et al, 2022;Marinova et al, 2010;Ocampo et al, 2018;Organ, 1994) According to Zia et al (2022), organizational members with Islamic organizational citizenship behavior will exhibit behavior that reflects the values of goodness in Muslims. However, research on organizational members' behavior has been dominated by Western values, and there is still a lack of research considering the Islamic values perspective.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation